A Critical Review of the Book Violence and Social Orders: A Conceptual Framework for Interpreting Recorded Human History - Ali Karimi Maleh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article aims at the critical study of the book Violence and Social Orders written by North and his colleagues. Political violence is a frequent phenomenon and has great consequences in the political life of societies. Hence, it has attracted many social and political scientists since ancient times. The rise of new forms of political violence from the beginning of the third millennium, caused its reconsideration by different thinkers. This book by North and his colleagues is considered as a pioneer and creative work regarding the issue of violence and its relationship with development from the perspective of political economy and historical-comparative approach to provide a conceptual framework for understanding and analyzing ways of control of political violence in limited access social orders and open access social orders. The main idea of the book examines the basic rationale of social orders and the explanation of the transition from natural governments to open access orders and reduction of violence through the coalition of elites or political and economic competition. In spite of various innovative and creative ideas presented in this book, its critical reading, represents some shortcomings such as reductionist understanding of the political violence, teleological and ideological understanding of the open-access order and acceptance of modernization paradigm and uni-linearism in the transformation of societies and the neglect of the asymmetrical and hierarchical relations between developed and developing countries.